Quantification of delay factors using the relative importance index method for construction project - Nor Fatini, Mohd Rasip (2016)
Construction known in general as an activity involve of clearing, dredging, excavating and grading of land and other activity associate with building, structure and other types of structure such as bridges, dams and roads. In the real situation, every project of construction will face a delay. Delay commonly happen in large project as it involved many parties. As a result, many major projects fail to meet schedule deadlines. The aim of this research is to identify the delay factors of construction projects on view of contractor and analyze these factors with the Relative Importance Index Method. For this purpose, 25 different delay factor were identify and categories in 5 major factor. The main major factor is contractor related factor, consultant related factor, design related factor, equipment related factor and external related factor. The Relative Importance Index (RII) is calculate for each factor and ranking it from the highest value to the lower value. The highest value of Relative Importance Index (RII) is known as a major factor of delay in construction project. Some of the recommendation and suggestion from the respondent are contractors should have experience before the bidding stage. Plus, project manager should preparing effective planning and scheduling to make sure the progress run smoothly.